Conformal isoparametric spacelike hypersurfaces in conformal spaces $\mathbb{Q}^4_1$ and $\mathbb{Q}^5_1$ - Bianping, Su; Shu, Shichang (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the conformal geometry of conformal spacelike hypersurfaces in the conformal spaces $\mathbb{Q}^4_1$ and $\mathbb{Q}^5_1$. We obtain a complete classification of conformal isoparametric spacelike hypersurfaces in $\mathbb{Q}^4_1$ and $\mathbb{Q}^5_1$.